Phenformin alone or combined with gefitinib inhibits bladder cancer via AMPK and EGFR pathways - Yanjun Huang; Sichun Zhou; Caimei He; Jun Deng; Ting Tao; Qiongli Su; Kwame Oteng Darko; Mei Peng; Xiaoping Yang (Cancer Communications, 2018)
Abstract Background In previous studies, we have shown that the combination of metformin and gefitinib inhibits the growth of bladder cancer cells. Here we examined whether the metformin analogue phenformin, either used alone or in combination with gefitinib, could inhibit growth of bladder cancer cells. Methods The growth-inhibitory effects of phenformin and gefitinib were tested in one murine and two human bladder cancer cell lines using MTT and clonogenic assays. Effects on cell migration were assessed in a wound healing assay. Synergistic action between the two drugs was assessed using CompuSyn software. The potential involvement of AMPK and EGFR pathways in the effects of phenformin and gefitinib was explored using Western blotting. Results In MTT and clonogenic assays, phenformin was > 10-fold more potent than metformin in inhibiting bladder cancer cell growth. Phenformin also potently inhibited cell migration in wound healing assays, and promoted apoptosis. AMPK signaling was activated; EGFR signaling was inhibited. Phenformin was synergistic with gefitinib, with the combination of drugs showing much stronger anticancer activity and apoptotic activation than phenformin alone. Conclusions Phenformin shows potential as an effective drug against bladder cancer, either alone or in combination with gefitinib.